The Ketogenic Diet: Safety, Morbidity, and Mortality - Taufiqurrachman Nasihun (Universitas Sultan Agung Semarang, 2019)
In normal daily diet consisting of 52-55% carbohydrate, 32-34% fat, and 14-18% protein, a couple hours following meal and absorption there is abundant fuel supply particularly from glucose oxidation in most tissues (Kathleen M Botham and Mayes, 2015; USDA, 2015). Conversely, in ketosis condition, most tissues replace its energy requirement from glucose to ketone bodies resulting from hepatic ketogenesis (Cervenka and Kossoff, 2013; Mcdonald and Cervenka, 2017). In extra hepatic tissues, adenosine triphosphate (ATP) is synthesized through revert back of acetoacetate to acetoacetyl-CoA catalyzed by succinyl-CoA-acetoacetate CoA transferase. By this reaction acetoacetyl-CoA is split into two acetyl-CoA catalyzed by thiolase and then inserted into Kreb’s cycle to form ATP. Acetoacetate and b hydroxybutyrate are also able to traverse blood brain barrier and metabolized by cellular brain into ATP and used as energy also postulated as anticonvulsant (Freeman et al., 2007; J. L. Gamble et al., 1923). Moreover, when ketone bodies in circulation are increased, oxidation of ketone bodies also raised until saturation of the pathway is achieved at 12 mmol/L concentration (Kathleen M. Botham and Mayes, 2015). Concern to the energy synthesis, acetoacetate and 3-b hydroxybutyrate are the prominent ketone bodies which are readily oxidized in extra-hepatic tissues. Whilst acetone have not metabolic function and in large extent is volatilized through the lung marked by breathe odor (Kathleen M. Botham and Mayes, 2015; Paoli, 2014). Ketosis is also able to suppress hunger feeling and appetite, therefore potential to be a good regulator of the body’s calorie intake (Dashti et al., 2004).  However, ketosis which is induced by ketogenic diet (KD), in the long term, its safety, morbidity, and mortality remain inconclusive.